Adalimumab improves joint-related and skin-related functional impairment in patients with psoriatic arthritis: patient-reported outcomes of the Adalimumab Effectiveness in Psoriatic Arthritis Trial. Issue 2 (17th October 2006) - Gladman, D D; Mease, P J; Cifaldi, M A; Perdok, R J; Sasso, E; Medich, J
Abstract : Objective: To evaluate the effects of adalimumab on patient-reported outcomes of joint-related and skin-related functional impairment, health-related quality of life, fatigue and pain in patients with psoriatic arthritis (PsA). Methods: Patients with moderately- to severely- active PsA were treated with adalimumab, 40 mg, every other week, or placebo, in this 24-week, randomised, controlled trial. Patient-reported outcomes included the Health Assessment Questionnaire Disability Index (HAQ DI), Short-Form 36 Health Survey (SF-36), the Functional Assessment of Chronic Illness Therapy—Fatigue (FACIT-Fatigue) Scale and the Dermatology Life Quality Index (DLQI). Results: Adalimumab (n = 151) and placebo (n = 162) groups were comparable with respect to baseline demographics and disease severity. Significant changes from baseline in HAQ DI were reported for adalimumab v placebo (−0.4 v −0.1, p<0.001) at both 12 and 24 weeks. At week 24, significant improvements in the SF-36 domains of physical functioning, role-physical, bodily pain, general health, vitality and social functioning, as well as the physical component summary score, were observed for adalimumab versus placebo (p<0.01). These reported changes in HAQ DI and SF-36 were also clinically important. Significantly more patients treated with adalimumab had complete resolution of functional loss (HAQ DI = 0) and dermatological-related functional limitations (DLQI = 0) compared with placebo at weeks 12 and 24 (p⩽0.001). Adalimumab led to significantly greater improvements in FACIT-Fatigue scores, pain scores, and disease activity measures versus placebo at 12 and 24 weeks (p<0.001 for all). Conclusions: Adalimumab improved physical-related and dermatological-related functional limitations, HRQOL, fatigue and pain in patients with PsA treated for 24 weeks.